3D-bioprinting of patient-derived cardiac tissue models for studying congenital heart disease - Wolfe, Jayne T.; He, Wei; Kim, Min-Su; Liang, Huan-Ling; Shradhanjali, Akankshya; Jurkiewicz, Hilda; Freudinger, Bonnie P.; Greene, Andrew S.; LaDisa, John F.; Tayebi, Lobat; Mitchell, Michael E.; Tomita-Mitchell, Aoy; et al. (Frontiers in Cardiovascular Medicine, 2023)
Congenital heart disease is the leading cause of death related to birth defects and affects 1 out of every 100 live births. Induced pluripotent stem cell technology has allowed for patient-derived cardiomyocytes to be studied in vitro. An approach to bioengineer these cells into a physiologically accurate cardiac tissue model is needed in order to study the disease and evaluate potential treatment strategies. To accomplish this, we have developed a protocol to 3D-bioprint cardiac tissue constructs comprised of patient-derived cardiomyocytes within a hydrogel bioink based on laminin-521. Cardiomyocytes remained viable and demonstrated appropriate phenotype and function including spontaneous contraction. Contraction remained consistent during 30 days of culture based on displacement measurements. Furthermore, tissue constructs demonstrated progressive maturation based on sarcomere structure and gene expression analysis. Gene expression analysis also revealed enhanced maturation in 3D constructs compared to 2D cell culture. This combination of patient-derived cardiomyocytes and 3D-bioprinting represents a promising platform for studying congenital heart disease and evaluating individualized treatment strategies.